Efficient Synthesis of Esters by Cleavage of C–S and C–N Bonds via Alkylation and Activation of Thioamides - Vankar, Jigarkumar K.; Jadav, Jaydeepbhai P.; Gururaja, Guddeangadi N. (Synthesis, 2024)
A mild and efficient reaction for synthesizing esters from thioamide precursors has been established. This method is accomplished in one pot under mild conditions. The process involves the alkylation and activation of inert thioamides, which leads to the cleavage of stable C–N and C–S bonds, eventually resulting in valuable esters with a broad range of substrates. The transformation can be easily carried out at room temperature using thioamide substrates, reactants, and activating agents. This protocol has been demonstrated by synthesizing important esters with applications.
Keywords: thioamides; alkylation; activation; ester; amines